(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article provides a systematic examination of the hygienic rules for the use of cosmetic products, focusing on health, dermatological safety, and microbiological risk. Data from empirical and laboratory studies are analyzed, including microbiological contamination of cosmetic applicators and products, adverse skin reactions, users’ hygienic behaviors, and the role of storage conditions. Preventive measures — product selection, individual use, cleaning of applicators, storage, and educational outreach — are also discussed. The study results aim to inform practical recommendations for cosmetic hygiene and to improve regulatory policies within public health systems.